Influence of added zinc from zinc oxide on starter pig performance - J C Woodworth; P R O'Quinn; T M Fakler; Michael D Tokach; Jim L Nelssen; Robert D Goodband; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1998)
Three hundred and sixty early-weaned barrows were fed diets containing increasing levels of added Zn from zinc oxide (0, 50, 100, 200, 400, 800, 1,600, 2,400, and 3,200 ppm). From d 11 to 21, growth performance improved with up to 100 ppm of added Zn but was not improved further until pigs were fed 3,200 ppm of added Zn. From d 21 to 36, pigs fed 100 ppm of Zn had the best growth performance. These results suggest that a pig's basal Zn requirement is met with 100 ppm of added Zn from zinc oxide, but adding 3,200 ppm Zn in early starter diets results in further growth promotion. For these reasons, 3,200 ppm Zn from zinc oxide should be added to diets fed from weaning (8 to 10 lb) until 15 lb and a reduced amount in subsequent diets.; Swine Day, Manhattan, KS, November 19, 1998
Keywords: Swine day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 819; Swine; Early-weaned pigs; Growth; Zinc